2000
DOI: 10.1029/1999jd901122
|View full text |Cite
|
Sign up to set email alerts
|

Effects of snow physical parameters on spectral albedo and bidirectional reflectance of snow surface

Abstract: Abstract. Observations of spectral albedo and bidirectional reflectance in the wavelength region of X = 0.35-2.5 tzm were made together with snow pit work on a flat snowfield in eastern Hokkaido, Japan. The effects of snow impurities, density, layer structure, and grain size attained by in situ and laboratory measurements were taken into account in snow models for which spectral albedos were calculated using a multiple-scattering model for the atmosphere-snow system. Comparisons of these theoretical albedos wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
295
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 271 publications
(312 citation statements)
references
References 36 publications
17
295
0
Order By: Relevance
“…Snow grain size has long been used as a substitute for SSA (Gow, 1969), but given the variety of grain shapes, from dendritic to rounded to hollow, the definition of grain size is ambiguous and observer-dependent (Aoki et al, 2000). With the example of hollow depth hoar crystals, Taillandier et al (2007) have shown that effective grain size deduced from SSA (Eq.…”
Section: Introductionmentioning
confidence: 99%
“…Snow grain size has long been used as a substitute for SSA (Gow, 1969), but given the variety of grain shapes, from dendritic to rounded to hollow, the definition of grain size is ambiguous and observer-dependent (Aoki et al, 2000). With the example of hollow depth hoar crystals, Taillandier et al (2007) have shown that effective grain size deduced from SSA (Eq.…”
Section: Introductionmentioning
confidence: 99%
“…The grain diameter is not unequivocally defined in the literature, which is understandable since the definition of snow grain itself is often ambiguous. There is a consensus for expressing grain effective diameter as proportional to the ratio of crystal volume to projected area, but the value of the multiplier can vary according to the specific choice of the author Kokhanovsky and Zege, 2004;Aoki et al, 2000). In line with several recent publications (see, for example, Zege et al, 2011;Jin et al, 2008), we define it as 3/2 times the ratio of the crystal volume over its surface area, as outlined in Appendix A, which includes the details of the relationship to geometric size.…”
Section: Methodsmentioning
confidence: 91%
“…For the retrieval of crystal habit, the polarized reflectance at 864 nm is used because of the very weak ice absorption at this wavelength and the relatively weak Rayleigh scattering contribution. Ice crystals are found to vary within a virtually countless set of shapes, but, limited by the lack of constraints on the correct optical properties, very few studies have departed from the common practice of assuming spherical shapes for the snow grains, an approximation which can negatively impact the quality of the albedo products (Tedesco and Kokhanovsky, 2007;Aoki et al, 2000). Among the available optical models for non-spherical grains are for example those of Baum et al (2011Baum et al ( , 2014 and Yang et al (2013).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, precise estimation of the radiation budget is necessary for detecting such drastic environmental changes in the cryosphere, quantifying the areas and volume of melting ice, and understanding the effects of ice-albedo feedback mechanisms. The relationships between shortwave albedo and snow physical parameters such as snow grain size and impurities have been studied frequently (Aoki et al, 2000;Stamnes et al, 2007;Aoki, et al, 2007;Hori et al, 2007;Painter et al, 2009;Kuchiki et al, 2009). On the contrary, longwave emission from snow cover is usually considered to exhibit blackbody-like behavior, and the dependences of emissivity on snow type are usually ignored in remote sensing applications.…”
Section: Introductionmentioning
confidence: 99%